Frequency and level of self-efficacy predict the effectiveness of therapist- and self-guided exposure in obsessive compulsive disorder. Issue 6 (20th November 2020) - Voderholzer, Ulrich; Hilbert, Sven; Fischer, Anne; Neumüller, Jakob; Schwartz, Caroline; Hessler-Kaufmann, Johannes Baltasar
Abstract: Background: While exposure and response prevention (ERP) is the most effective treatment for obsessive compulsive disorder (OCD), less is known about the specific mechanisms underlying symptom change after ERP. Aims: We tested the hypothesis that the frequency of self- and therapist-guided ERP related to the extent of symptom reduction and that this link is mediated by increased self-efficacy. Method: In a sample of 377 in-patients with a primary diagnosis of OCD receiving in-patient CBT, we assessed symptoms (YBOCS-SR) and self-efficacy (General Self-Efficacy Scale), before and after treatment, as well as the frequency of therapist- and self-guided ERP sessions. Results: Patients with more therapist-guided ERP sessions during treatment showed more symptom reduction and the association of self-guided ERP on outcome was mediated by enhanced self-efficacy. Conclusions: These findings highlight the importance of both therapist- and self-guided ERP sessions and suggest that therapists should conduct a sufficient number of ERP sessions to optimise treatment.